First report on degradation of Alternaria toxins in apple juice by UV-C treatment - Ayranci, Ufuk Gokce; Karaca, Hakan (Frontiers in Nutrition, 2026)
Toxic metabolites of Alternaria spp. are considered as “emerging mycotoxins” and have not been yet regulated by legislation in many countries. Alternaria species can grow and produce these mycotoxins in various products including fruits and fruit juices. In the present study, UV-C treatment (3971.09 J m−2, 1–8 h) was used for the first time to degrade Alternaria toxins [tenuazonic acid (TeA), alternariol (AOH) and alternariol monomethyl ether (AME)] in apple juice. The effect of the treatment on quality characteristics of apple juice was also evaluated. UV-C treatment was very effective in degrading toxins. AME was the most affected toxin (decreased by half) after a treatment for 1 h. Degradation rates of 90.52, 77.01 and 75.92% were observed in the levels of TeA, AOH and AME, respectively, at the end of treatment for 8 h. Soluble solid content, pH and titratable acidity values did not change significantly after UV-C treatment, however turbidity values increased by 92% at the end of treatment. One of the major effects of UV-C treatment was on the color of the apple juice. Transmittance value at 440 nm increased while a* and b* values decreased significantly (p < 0.05) which shows that UV-C had a deleterious effect on color pigments of the juice. Significant decreases were observed also in phenolic content and antioxidant activity of the UV-C treated juice. These results demonstrate that UV-C is quite effective in degrading Alternaria toxins in apple juice but has detrimental effects on some quality characteristics, especially for prolonged treatment periods.